Factors contributing to failures in projects developed by Bumiputera contractor (Askme Sdn Bhd) / Nornadirah Mohd Razali - Mohd Razali, Nornadirah (Faculty of Business and Management, 2007)
The construction industry is an important sector of every economy, which nevertheless has not been studied in detail. This basic paper offers a fundamental description of the construction industry and offers the features of Malaysia construction industry. Otherwise, it describes problems facing the industry and takes a well established theory and studies and applies it to the construction projects research. The purpose of this research is to determine factors contributing to failures among Bumiputera contractor (Askme Sdn Bhd). The researcher completed an adapted version of the Construction questionnaire, which asked the respondents to attribute causes that can be factors along a number of sites projects which have failed. Focus is placed on Askme Sdn Bhd management and technical team, suppliers and clients. The factors are the attitudes, capital and capabilities of the Bunliputera contractors and were tested by using a Statistical Package for Social Science. Other factors related to economic environment in construction industry were also asked in the questionnaires. The results indicate that attitudes, capital and capabilities have contributed to failures in sites projects which have done by Askme Sdn Bhd. Apart from that, economic environment in construction industry have also contributed to failures among them. It can be concluded that this study is essential for Askme Sdn Bhd in order to identify factors such as their attitudes, capabilities and failures that might contributing to failures in certain project developed by them. Thus, they may improve their performance in construction industry and able to compete with non-Bumiputera contractors.